ANALYSIS OF ABRATION RATE IN TELUK PAMBANG VILLAGE, KECAMATAN BANTAN BENGKALIS, RIAU PROVINCE - Simamora, Yohanna Beata; Galib, Musrifin; Elizal, Elizal (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
Abstract Teluk Pambang Village in Bengkalis Regency which is located in the Riau Province is one of the villages that is very vulnerable to abrasion, because it is an area that faces the Malacca Strait and has a peat texture. This study examined how much the abrasion rate and the extent of the shoreline changes that occurred in Teluk Pambang Village by using Landsat satellite imagery data in the last 20 years. Landsat satellite image data processing consists of geometric calibration, image cutting, image sharpening and digitization so that the coastline position for each data year is obtained. Changes in the coastline from year to year are analyzed by the process of overlapping data for a certain period of time. The results of this study indicate that Teluk Pambang Village experiences abrasion with varying levels of abrasion. changes in coastline Teluk Pambang Village The last 20 years from 1997 - 2017 there was an abrasion of 4.18 m / year and sedimentation of 5.33 m / year. The change of coastline in Teluk Pambang Village is abrasion of 418.88 m and sedimentation area of 218.28 m. There is a positive relationship of current velocity with abrasion velocity and abrasion velocity relationship with wave energy obtained from linear regression results on the graph.Critical beaches that experience maximum abrasion rates are recommended to be immediately addressed so that abrasion does not continue in subsequent years.Keywords: Abrasion, Accretion, Landsat Image, Coastline, TelukPambang Village